The neurovascular complexity index as a potential indicator of traumatic brain injury severity: A case-series study. Issue 1 (July 2017) - Howard, Jeffrey T.; Janak, Jud C.; Bukhman, Vladislav; Robertson, Claudia; Frolov, Iurii; Nawn, Corinne D.; Schiller, Alicia M.; Convertino, Victor A.
Abstract : BACKGROUND: Multimodal monitoring of brain physiology following a traumatic brain injury (TBI) shows promise as a strategy to improve management and outcomes of TBI patients within civilian and military trauma. Valid and reliable measures of different aspects of brain physiology following a TBI could prove critical to accurately capturing these changes. METHODS: Using a case-series design with a control subject group comparison, we evaluated a new proprietary algorithm called the Neurovascular Complexity Index (NCI) using transcranial Doppler to noninvasively obtain measures of cerebral blood flow variability. Baseline NCI data from 169 control subjects were compared with 12 patients with moderate to severe TBI. RESULTS: Patients with TBI exhibited significantly greater mean and variability in NCI scores compared with control subjects (F = 195.48; p < 0.001). The mean absolute deviation (MAD) of NCI scores increased significantly and in a monotonic fashion with severity of injury, where control subjects exhibited a small MAD of 0.44, patients with moderate TBI had a higher MAD of 4.20, and patients with severe TBI had an MAD of 6.51 ( p < 0.001). CONCLUSIONS: Advancement in multimodal monitoring of TBI patients is important in reducing the potential risk of secondary injury. This study reports results indicating that a new noninvasive quantifiable assessment of TBI based on a noninvasive measure of cerebral blood flow variability shows potential for continuous monitoring and early identification of brain-injured patients, deployable in far-forward military environments, to better inform individualized management. Level of Evidence: Case series, level IV.